Dual Challenge of Cancer and COVID-19: Impact on Health Care and Socioeconomic Systems in Asia Pacific - De Guzman, Roselle (JCO Glob Oncol, 2020)
Coronavirus or COVID-19 is caused by severe acute respiratory syndrome coronavirus 2. The COVID-19 pandemic has resulted in social and economic disruption throughout the entire world. Each country is being challenged. Although much of the world’s focus has been on the rapid spread in Italy, Spain, and the United States, the potential impact on the world’s poor, a majority of whom are living in Asia, could be devastating. Asia has the world’s most densely populated cities, and its developing countries are facing challenges in their socioeconomic and health care systems. COVID-19 is quickly overwhelming the fragile and overstretched health systems of low- and low- to middle-income countries. With its aging population having chronic diseases and the growing burden of cancer, Asia is facing the dual challenge of controlling the spread of COVID-19 and at the same time providing and maintaining cancer care.